Macroprudential policy at the ECB: Institutional framework, strategy, analytical tools and policies - Inês Cabral; Carsten Detken; John P. C. Fell; Jérôme Henry; Paul Hiebert; Sujit Kapadia; Sergio Nicoletti-Altimari; Fátima P. dos Santos; Carmelo Salleo (European Central Bank (ECB), 2019)
This occasional paper describes how the financial stability and macroprudential policy functions are organised at the ECB. Financial stability has been a key policy function of the ECB since its inception. Macroprudential policy tasks were later conferred on the ECB by the Single Supervisory Mechanism (SSM) Regulation. The paper describes the ECB's macroprudential governance framework in the new institutional set-up. After reviewing the concept and origins of systemic risk, it reflects on the emergence of macroprudential policy in the aftermath of the financial crisis, its objectives and instruments, as well as specific aspects of this policy area in a monetary union such as the euro area. The ECB's responsibilities required new tools to be developed to measure systemic risk at financial institution, country and system-wide level. The paper discusses selected analytical tools supporting financial stability surveillance and assessment work, as well as macroprudential policy analysis at the ECB. The tools are grouped into three broad areas: (i) methods to gauge the state of financial instability or prospects of near-term systemic stress, (ii) measures to capture the build-up of systemic risk focused on country-level financial cycle measurement and early warning methods, and (iii) the ECB stress testing framework for macroprudential purposes.
Keywords: E37; F36; G20; G28; K23; 330; Financial stability; financial imbalances; macroprudential; systemic risk; stress testing; financial regulation; SSM; ESRB; monetary policy